Perkembangan Fisik Kota Lhokseumawe: Tinjauan Terhadap Penataan Ruang Kawasan Pusat Kota - Muhyi, Abdul (Jurnal Tata Kota dan Daerah, 2016)
The Dynamic of Lhokseumawe is interesting to study for its role as atransit town as well as the capital of Lhokseumawe municipality implicating in the intensity and kinds of urban sosio-economic activities and seen from the exsisting patterns of intensity and development of urban land use, movement orientation, road network, and other urban facilities. This study aims to examining the mechanism of urban natural physica development and the patterns and direction of 1992-2012 physical development of Banda Sakti, one of the sub-disstricts of Lhoksemawe, and learning the elements of urban physical changes and the mechanism of their spstial and sectoral movement describing the real development of the fungtions of urban spaces in detail to be used in planning the future development of Lhokseumawe. Primary data for this study were collected through an interview while the secondary data were obtained from related institutions and then reanalyzed by using the rationalistic-quantitative approach to examine several aspects used in studying the town of Lhokseumawe with gradual emphasis in 1992, 2002 and 2012. The physical development of Lhokseumawe tends of follow the pattern of linier area development on both sides of existing road that empty spaces are found between the areas developed. In addition, the physical development of the town of lhokseumawe is very much influenced by an impetus such as the expansive land price downtown while the downtown itself has asignificant attraction because of the exsistence of hausing facilities, local markets, local transportation terminal, office facilities, two states universities which are close to regional road.Keywords: urban development, urban physic, spatial plan.